Modulation of phenolic production in Vitis vinifera cell cultures with Phaeomoniella chlamydospora and other elicitors - Lima, M. R. M. (2005)
Esca is a destructive disease that affects Vitis vinífera plants around the world leading to important losses in wine production. Phaeomoniella chlamydospora (Pc) is a fungus frequently associated with esca and grapevine decline. Information on the interaction of this fungus with Vitis vinifera is scarce. To study the defense mechanisms of Vitis plants to Pc we utilized cell suspension cultures of V. vinifera cv. Vinhão (Vv) elicited with fungus Pc, methyl-jasmonate (MeJ) and salicylic acid (SA). We also used cultures primed with MeJ or SA 24h before elicitation with Pc (MeJ+Pc or SA+Pc, respectively). Several culture samples were taken during the experimental period and phenolic production was evaluated by HPLC-DAD-MS